2008
DOI: 10.1177/1541204007313382
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Police Contact Among Midwestern Homeless and Runaway Youth

Abstract: Research has substantiated that homeless and runaway youth are at high risk for offending and deviant behavior. Although gender, abuse, and deviant peers have been implicated in arrests among homeless youth, we know less about whether these precursors operate similarly for police harassment as well as for postrunaway arrest. In a study of 361 Midwestern homeless and runaway youth, several differences were noted between the predictors of arrest and police harassment. First, path-analytic techniques demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Of the 10 studies reporting on CJI, 6 studies reported assessing CPA. A history of CPA was associated with increased risk of committing offenses in adult homeless veterans (Benda, Rodell, & Rodell, 2003); serious violent crimes in recently released homeless paroled men (Nyamathi et al, 2012); criminal behaviors of female homeless runaways and adults (Simons & Whitbeck, 1991); and delinquent behavior, arrest, and being hassled by police (Thrane et al, 2008) and arrest and ever being in jail (Yoder et al, 2014) among homeless youth. Only one study did not find any relationship between CPA and incarceration history among homeless adults (Saddichha et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 studies reporting on CJI, 6 studies reported assessing CPA. A history of CPA was associated with increased risk of committing offenses in adult homeless veterans (Benda, Rodell, & Rodell, 2003); serious violent crimes in recently released homeless paroled men (Nyamathi et al, 2012); criminal behaviors of female homeless runaways and adults (Simons & Whitbeck, 1991); and delinquent behavior, arrest, and being hassled by police (Thrane et al, 2008) and arrest and ever being in jail (Yoder et al, 2014) among homeless youth. Only one study did not find any relationship between CPA and incarceration history among homeless adults (Saddichha et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to CM, and in particular CPA and CSA, is one of the most significant predictors of criminal justice involvement (CJI) and victimization among homeless populations (Thrane, Chen, Johnson, & Whitbeck, 2008; Yoder, Bender, Thompson, Ferguson, & Haffejee, 2014). In fact, exposure to CM is the primary reason for running away from home and early homelessness (Mar, Linden, Torchalla, Li, & Krausz, 2014) which consequently amplifies the risk of involvement with antisocial peers, substance abuse, deviant subsistence strategies, and engaging in survival behaviors (e.g., panhandling, theft, drug dealing, and prostitution; Whitbeck, Hoyt, & Yoder, 1999).…”
mentioning
confidence: 99%
“…Similarly, Thrane et al (2008) noted that 55% of their sample had been arrested and 45% reported being hassled by the police. Whitbeck and Hoyt (1999) found that 42% of females and 34% of males had been arrested or spent some time in juvenile detention.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Youth in these situations may avoid shelter and other programs, because they know they would not be able to stay at the shelter while intoxicated and may be referred for treatment. As such, non-service usage youth may be more likely to spend their time on the street, which not only increases their risk for victimization (Tyler et al, 2004) but also increases their chances of associating with deviant peers, which has been found to strongly influence the likelihood of being harassed or arrested by the police (Chapple et al, 2004; Thrane et al, 2008). …”
Section: Literature Reviewmentioning
confidence: 99%
“…In Canada, youth are more often accused of committing crimes than people of other ages (Allen, 2018) and among PWUD, youth are more likely to encounter police and perceive these encounters as negative (Greer et al, 2018). Evidence from North America (Thrane et al, 2008; Ti et al, 2013) and elsewhere (Busza et al, 2013) demonstrates that using drugs, especially in public spaces, increases targeting and harassment of youth by police and confiscation of drug equipment and violence by police. It is important to recognize that such encounters take place in the context of a war on drugs and the criminalization and stigmatization of illicit drugs that is rooted in inequitable drug policies (Lloyd, 2013; UK Drug Policy Commission, 2011; United Nations High Commission for Human Rights, 2015; United Nations Office on Drugs and Crime [UNODC], 2018).…”
Section: Literature Reviewmentioning
confidence: 99%